Prostatectomy using different lasers for the treatment of benign prostate hyperplasia in aging males - Lee WC (Dove Medical Press, 2013)
Wei-Chang Lee,1,* Yu-Hsiang Lin,1,* Chen-Pang Hou,1 Phei-Lang Chang,1 Chien-Lun Chen,1 Horng-Heng Juang,2 Ke-Hung Tsui1 1Department of Urology, Chang Gung Memorial Hospital-Linko and Chang Gung University, College of Medicine, Taiwan, 2Department of Anatomy, College of Medicine, Chang Gung University, Kweishan-Shan, Taoyuan, Taiwan, Republic of China *These authors contributed equally to this work Purpose: Endoscopic lasers have become a treatment option for benign prostate hyperplasia (BPH). The study reported here sought to elucidate the benefits and drawbacks of different laser systems in the treatment of patients with BPH. Methods: The study enrolled 741 patients diagnosed with lower urinary tract symptoms secondary to BPH during the period January 2005 to December 2011. The techniques used in the study were photoselective vaporization of the prostate, thulium laser prostatectomy, and diode laser prostatectomy. Patients were assigned to one of three groups according to the type of laser treatment they received. Outcomes were evaluated using the International Prostate Symptom Score (IPSS), quality of life, maximal urinary flow rate, post-voiding residual urine volume, and prostate-specific antigen (PSA) level. Results: The baseline characteristics of patients who received diode laser prostatectomy show a significant elevated risk and high American Society of Anesthesiology score (P=0.001). Operative time and catheter removal time differed significantly between the three groups (P=0.001). No cases were converted to transurethral resection of the prostate intraoperatively due to bleeding (P=0.142). Among the three groups, there were no significant differences in maximal flow rate, lower post-void residual urine, and postoperative PSA level during the entire follow-up period (P<0.05). Further, no significant differences in postoperative IPSS, quality of life, or bladder neck contracture (P=0.23) were observed. However, a significant difference was observed with regard to prolonged use of Foley catheters and prolonged hospital stay among patients in the diode laser group (P=0.001). Conclusion: Laser prostatectomies are effective in dealing with lower urinary tract symptoms. Early subjective functional results (maximal flow rate, IPSS, and post-void residual urine) appeared the same as those obtained following laser prostatectomy. Thus, it appears that lasers are safe and effective as long as the patients are carefully selected for treatment. Keywords: prostate gland, laser prostatectomy, diode laser, thulium laser, photoselective vaporization of the prostate